2015
DOI: 10.1080/10599231.2015.997625
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, International Trade, and Economic Growth in Australia: New Evidence From Multivariate Framework Analysis

Abstract: This study investigates the relationship between financial development, international trade and economic growth in case of Australia over the period of 1965-2010. The ARDL bounds testing approach to cointegration was applied to examine the long run relationship among the series, while stationarity properties of the variables were tested by applying two structural break tests i.e. Zivot-Andrews (1992) and Clemente et al. (1998).Our empirical evidence confirmed the long run relationship among the variables. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The FMOLS and DOLS results indicate that trade openness, money supply, and gross capital formation are positively related to economic growth. Our findings support (Bal et al, 2016; Kar et al, 2011; Murthy et al, 2014; Odhiambo, 2009; Rahman et al, 2015; Sehgal et al, 2013; Sehrawat & Giri, 2016a; Uddin et al, 2016). Other interesting result derived from the study is that inward FDI negatively associated with economic growth in BRICS nations.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…The FMOLS and DOLS results indicate that trade openness, money supply, and gross capital formation are positively related to economic growth. Our findings support (Bal et al, 2016; Kar et al, 2011; Murthy et al, 2014; Odhiambo, 2009; Rahman et al, 2015; Sehgal et al, 2013; Sehrawat & Giri, 2016a; Uddin et al, 2016). Other interesting result derived from the study is that inward FDI negatively associated with economic growth in BRICS nations.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 86%
“…The results confirmed that there is long-run relationship among inward FDI, trade openness, broad money, DC to private investors, gross capital formation, and GDP per capita in both the model. The long-run relationship between financial development, trade openness, and economic growth is supported by several researchers (Kakar & Khilji, 2011; Kar et al, 2011; Murthy et al, 2014; Odhiambo, 2009; Rahman et al, 2015; Sehgal et al, 2013; Sehrawat & Giri, 2016a; Uddin Bidisha, & Ozturk, 2016). In addition, the study used FMOLS and DOLS methods to investigate the degree of long-run coefficient.…”
Section: Results and Interpretationmentioning
confidence: 92%
“…In addition to the results, in all other sectors except MC and CH sectors, causality relation was observed at different rates from credit interest rates to industrial production index. There are also some studies in the literature in which the causality relation from bank credits to industrial production index is partially or completely observed (Toby and Peterside, 2014;Chisasa, 2014;Rahman et al, 2015;Stolbov, 2017;Qamruzzaman and Jianguo, 2017) However, there are also studies in which the causality relationship from bank loans to industrial production index cannot be found (Dal Colle, 2011;Marques et al, 2013;Tripathi and Kumar, 2015;Adeola and Ikpesu, 2016). The casual relationship between the industrial production index and the bank credit volume and credit interest rates give clues that production is financed by bank loans.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Polat et al (2014) document the complementary effect of trade liberalization on finance-growth nexus in South Africa. Rahman et al (2015) investigated the said phenomenon in Australia and found a complementary role of trade in growth-finance nexus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since 1980s, most of the SAARC countries adopted trade liberalization policies to accelerate economic growth, which makes it interesting to investigate whether SAARC countries materialized the potential gain from this outward-oriented trade regime in terms of economic growth. Keeping in view this tendency of outward-oriented trade policies, most recently, some studies investigated trade openness for its effects on the finance-growth nexus and supported the claim (for instance, see Rahman et al, 2015;Asghar and Hussain, 2014;Polat et al, 2014).…”
Section: Introductionmentioning
confidence: 98%